The prospect of Internet democracy - Margolis, Michael; Moreno-Riano, Gerson (Ashgate Pub., 2009)
Focusing in particular on how political uses of the internet have affected or seem likely to affect patterns of influence among citizens, interest groups and political institutions, the authors examine whether the internet's impact on democratic politics is destined to repeat the history of other innovative ICTs.